Soil Sampling and Testing for the Home Landscape or Vegetable Garden - Amy L. Shober; Rao S. Mylavarapu (EDIS, 2009)
SL-281, a 6-page illustrated fact sheet by Amy L. Shober and Rao S. Mylavarapu, provides information for homeowners about taking a soil sample and submit it for testing and how to understand the soil test report. Published by the UF Department of Soil and Water Science, March 2009.